Crustal Heterogeneity of Antarctica Signals Spatially Variable Radiogenic Heat Production - L. Li; A. R. A. Aitken (Geophysical Research Letters)
Abstract Geothermal heat flow (GHF) is a key basal boundary condition for Antarctic ice‐sheet flow. Large‐scale variations are resolved by several recent models but knowledge of the smaller‐scale variations, crucial for ice sheet dynamics, is limited by unresolved variations in crustal radiogenic heat production. To define this at continent‐scale we use 3D gravity inversion constrained by seismic Moho estimates to identify variations in crustal composition and geometry beneath thick ice. Geochemically‐defined empirical relationships between density and heat production capture the global average trend and its variability, and allow to estimate from upper‐crust density spatial variations in radiogenic heat production. Significant variations are observed typically 1.2–1.6 μW/m3, and as high as 2 μW/m3 in West Antarctica. The contribution to GHF from these heat‐production variations is similarly variable, typically 16–24 mW/m2 and up to 60 mW/m2. The mapped variations are significant for correctly representing GHF in Antarctica.